Predictors for short-term successful weaning from continuous renal replacement therapy: a systematic review and meta-analysis. Issue 1 (31st December 2023) - Li, Yu; Deng, Xiaoqi; Feng, Jiaxing; Xu, Bo; Chen, Yulei; Li, Zhanying; Guo, Xiaodan; Guan, Tianjun
Abstract: The systemic review and meta-analysis aimed to identify the predictors for short-term successful weaning from CRRT in severe AKI patients. PubMed, Embase, the Cochrane Library, and grey literature were searched for relevant studies investigating variables for short-term successful weaning from CRRT to August 2022. Our criteria included patients with AKI who required CRRT but excluded patients with kidney failure. The pooled odds ratios (OR) and 95% confidence intervals (CI) were calculated using fixed-effect (I 2 ≤50% and P-value of the Q statistic > 0.1) or random-effect models (I 2 >50% or p-value of the Q statistic ≤ 0.1) as appropriate. Our search yielded 11 studies and described 11 variables. The pooled analysis showed that chronic kidney disease (OR = 0.638, 95% CI: 0.491–0.829), CRRT duration (OR = 0.913, 95% CI: 0.882–0.946), and urine output at the cessation of CRRT (per 100 mL/day increase) (OR = 1.084, 95% CI: 1.061–1.108) were predictive factors for short-term successful weaning from CRRT. Male (OR = 0.827, 95% CI: 0.627-1.092), diabetes mellitus (OR = 0.970, 95% CI: 0.761–1.237), and sepsis (OR = 0.911, 95% CI: 0.717–1.158) were unrelated to the short-term weaning from CRRT. The relationship between hypertension, use of vasopressors or inotropes at the starting of CRRT, use of vasopressors or inotropes at the cessation of CRRT, use of diuretics at the cessation of CRRT, serum creatinine at the cessation of CRRT, and short-term weaning from CRRT remains unclear. Additional prospective studies are needed to evaluate this relationship further.